If we build green, will it appraise? - Bently, Laura E. M. J., author; Glick, Scott, advisor; Strong, Kelly, advisor; Folkestad, James, committee member (Colorado State University. Libraries, 2014)
This study investigates the current status of sustainable value integration in real estate markets within Colorado. It was discovered that the property appraiser is in an opportunistic position to influence all stakeholders and potentially increase the demand for sustainable building practices. Therefore, the dynamics of the appraisal process, necessary inputs, and rules and regulations will be the main focus of the study. This research focus builds on the education and professional practices in both real estate and construction realms and therefore, has the potential to impact all professionals involved with any aspect of real estate property. This research uses an exploratory sequential mixed methods approach to conduct a cross-sectional study through archival research, a survey distribution, and the collection of quantitative and qualitative data. The investigation begins with a discovery of relevant terms to the study parameters and assessment of the necessary qualifications and processes to becoming a licensed appraiser, followed by a summary of the typical property appraisal process. Then, a comparative analysis of those sustainable education requirements and resources is conducted to discover the status of appraisal regulation and practices relative to sustainable building features. A survey was distributed to collect data on the perceptions of appraisal professionals toward the existence of sustainable value integration, the degree of their consideration, and their perspectives to its impact on economic value. The study confirmed that real estate appraisers in Colorado are progressing toward integrating sustainable building features in their appraisal assignments. However, the research confirmed several complex challenges to sustainable value integration exist: (1) sustainable feature recognition remains a challenge for a portion of the appraiser population, (2) appraisers are continually challenged by the inability to measure and quantify the economic impacts of sustainable building features, and (3) there is limited information and data related to sustainable building features available for appraisers to utilize in their analyses. Continuing efforts for mandated education focused on sustainability are needed. Further research is directed toward developing methods and processes to measure and quantify sustainable building features and their impacts, discovering efficient and accurate methods to record property and market data relative to sustainable building features, and case studies examining the impacts of specific building features and their influences on economic value.
Keywords: education; appraisal; integration; property; sustainability; value